Pengaruh Free Cash Flow Profitabilitas Likuiditas Kebijakan Utang Dan Collateralizable Assets Terhadap Kebijakan Deviden(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012 - 2014) - Sugesta, Rio Putra; , Dr. Fatchan Achyani, SE, M.Si (2017)
This research aims to analyze and obtain empirical evidence about the effects of free cash flow, profitability, liquidity, debt policy, and collateralizable assets to dividend policy. Independent variables were used free cash flow, profitability, liquidity, debt policy, and collateralizable assets. Dependent variable was used dividend policy. The research population was manufacturing companies listed in Indonesia Stock Exchange (IDX) in period of 2012-2014. Sample was collected by purposive sampling method. Total 57 manufacturing companies were taken as study's sample. Analysis method of this research used multiple regression. The results of this research showed that free cash flow, liquidity, debt policy, and collateralizable assets did not significantly effect to dividend policy. As for profitability has significantly effect to dividend policy. The determination coefficient result showed 20,1%. That's about 20,1% indicated the ability of the independent variables explained the dependent variable while 79,9% explained by the other variables. Keywords: Free Cash Flow, Profitability, Liquidity, Debt Policy, Collateralizable Assets, Dividend Policy